Pendampingan Penerapan Media Berbasis Animaker guna Meningkatkan Kualitas Guru PJOK - Silvi Aryanti; Iyakrus; Destriana; Destriani; Samsul Azhar; Karina Alisya Putri; Naila Zafhira Yunizar (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Teachers' pedagogical competence in organizing educational learning is through the use of learning media according to the characteristics of students. The problem found by junior high school physical education teachers in Ogan Ilir Regency is the lack of knowledge and utilization of science and technology in the form of animaker-based learning media, not yet understanding how to utilize Animaker optimally. The purpose of this community service activity is to provide training and mentoring on the application of animaker-based learning media to improve teacher skills. The methods used are lecture, question and answer and simulation methods. The results of community service activities, namely the pre-test results, can be seen that the interest of participants in participating in the service activities was 93.8%, experiencing an increase in the post-test of 6.2%. According to participants, 100% considered the importance of learning innovation in the digital era. The pre-test results regarding knowledge of animaker learning media were 44,8%, increasing after being given training materials and animaker mentoring by 55.2% during the post-test to 100%. Participants, 35.5%, knew how to operate animaker-based learning media according to the pre-test results, experiencing an increase of 64.5% during the post-test to 100%. The implication is that Animaker-based learning media can be applied as a reference for teaching materials for teachers. The conclusion is that training and mentoring activities using Animaker-based media for teachers have a positive impact, namely improving the quality of physical education teachers.